Tricky Isomers—The Evolution of Analytical Strategies to Characterize Plasmalogens and Plasmanyl Ether Lipids - Koch, Jakob; Watschinger, Katrin; Werner, Ernst R.; Keller, Markus A. (Frontiers in Cell and Developmental Biology, 2022)
Typically, glycerophospholipids are represented with two esterified fatty acids. However, with up to 20% a significant proportion of this lipid class carries an ether-linked fatty alcohol side chain at the sn-1 position, generally referred to as ether lipids and shaping their specific physico-chemical properties. Among those, plasmalogens represent a distinct subgroup characterized by a sn-1 vinyl-ether double bond. The total loss of ether lipids in severe peroxisomal defects such as rhizomelic chondrodysplasia punctata indicates their crucial contribution to diverse cellular functions. An aberrant ether lipid metabolism has also been reported in multifactorial conditions including Alzheimer’s disease. Understanding the underlying pathological implications is hampered by the still unclear exact functional spectrum of ether lipids. Especially in regard to the differentiation between the individual contributions of plasmalogens (plasmenyl lipids) compared to their non-vinyl-ether lipid (plasmanyl) counterparts. A primary reason for this is that an exact identification and quantification of plasmalogens and other ether lipids poses a challenging and usually labor-intensive task. Diverse analytical methods for the detection of plasmalogens have been developed. Liquid chromatography-tandem mass spectrometry is increasingly used to resolve complex lipid mixtures and with optimized parameters and specialized fragmentation strategies, a discrimination between ethers and plasmalogens is feasible. In this review, we recapitulate historic as well as current methodologies for the recognition and quantification of these important lipids and will discuss developments in this field that can contribute to the characterization of plasmalogens in high structural detail.